2017
DOI: 10.1002/pd.5184
|View full text |Cite
|
Sign up to set email alerts
|

Sex discordance identification following non‐invasive prenatal testing

Abstract: Sex chromosomes are the basis of sexual differentiation during embryonic development. Variations of the traditional XX or XY karyotype may result in conditions where the genotype is discordant with the phenotype. Detection of these conditions in the past typically occurred during adolescence, due to delayed puberty, or during adulthood, due to infertility. With the increasing availability of non-invasive prenatal testing and high-resolution ultrasound, more cases of genotype-phenotype sex discordance are being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 7 publications
2
45
0
Order By: Relevance
“…A case report involving a normal female by NIPT with male external genitalia in a routine fetal morphology assessment was first reported by Mansfield et alIn this work, a fetus with an unbalanced translocation involving the short arms of the X and Y chromosomes was described. Very recently, a series of cases have been reported on sex discordance following NIPT that highlights the many potential and complex explanations for these discordant results . A discrepancy in sex determination between chromosomal results and phenotypic manifestation is usually evident in the neonatal period or later at puberty.…”
Section: Discussionmentioning
confidence: 99%
“…A case report involving a normal female by NIPT with male external genitalia in a routine fetal morphology assessment was first reported by Mansfield et alIn this work, a fetus with an unbalanced translocation involving the short arms of the X and Y chromosomes was described. Very recently, a series of cases have been reported on sex discordance following NIPT that highlights the many potential and complex explanations for these discordant results . A discrepancy in sex determination between chromosomal results and phenotypic manifestation is usually evident in the neonatal period or later at puberty.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to calculate the incidence of discordant NIPS for fetal sex at our center because data for the total number of women tested with NIPS were unavailable. In a larger case series, the incidence of discordant NIPS sex chromosome results was reported as approximately 1 in 1500–2000 (Richardson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the traditional XX or XY fetal karyotype may result in conditions where the genotype is discordant with the phenotype (Richardson et al, ). Mansfield et al () reported diagnosis of a 46, XX male following NIPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations